PENERAPAN APLIKASI CHALLENGE WITH ERIN UNTUK PEMBELAJARAN PELAFALAN MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA JEPANG ANGKATAN 2020 UNIVERSITAS RIAU - Cahya Zuwmirrah; Mangatur Sinaga; Nana Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstrack:. This Study describes the implementation of the Challenge With Erin application forlearning pronunciation for 2020 Academic Year students of Japanese Language Education StudyProgram, Riau University. This research includes descriptive research, in the form of steps forimplementing the Challenge With Erin application for learning Japanese pronunciation. Thedata sources in this study were with 17 students of the Japanese Language Education StudyProgram 2020 Academic Year, Riau University. The method used in this research is qualitativemethod. The data was collected by using observation techniques, questionnaires, diaries, andtests. Data analysis was carried out by sorting the Challenge With Erin application steps. Theapplication of the Challenge With Erin application follows the method used by the creators ofThe Challenge With Erin application. The results of this study are, (1) Doing a zoom class, (2)Opening the class, (3) Introducing the Challenge With Erin application, (4) Conducting a pretest,(5) Delivering material, (6) Giving two quizzes, (7) Doing Posttest, (8) Clossing the Class.Key Words: application, challenge with erin, pronunciation